The The image of Russia in the Kosovo media discourse: comparison between the public and the private media - Tahiri, Lindita; Mavraj, Muhamet (Information & Media, 2019)
Considering the traditional role of Russia in excluding the Kosovo territories from the Albanian state, as well as the recent role of Russia in anti-Kosovo independence diplomatic lobbying, this study aims to identify the dominant narratives in Kosovo media about Russia by comparing three media outlets: the public service broadcaster RTK, the daily newspaper Koha Ditore and the online newspaper Gazeta Express. Different types of framing, such as titles, sources and attitudes are analysed; Critical Discourse Analysis (CDA) is used to highlight participants and the kind of actions they undertake in the journalistic discourse, raising questions about narrative choices and their ideological influence in the Kosovar audience. The results of the analysis show that the private outlets and in particular the online medium, which is popular amongst young audiences, tend to construct the affirmative image of the Russian leadership, especially regarding the portrayal of Vladimir Putin. While the affirmative reading for the Kosovar audience is privileged, other kinds of readings are suppressed, thus creating the ground for broader intended strategic objectives of political discourse.